Waste Power Plant Modeling Based Landfill Pretreatment and HCCI (Homogeneous Charge Compression Ignition) Generator Engine - Wahyu Hendra W; Gunawan Nugroho (IPTEK Journal of Proceedings Series, 2015)
Waste management is cruisal problem for major cities in all countries. Technically, MSW (Municipal Solid Waste) biological processes can be converted into LFG (landfill Gas), which can be used as an energy source for electricity generation. LFG utilization as fuel for power generation is also supported by the presence of motor fuel engines based HCCI (Homogeneous Charge Compression Ignition). To ensure the successful adoption of waste power plan based HCCI engine-generator, in the form of mathematical modeling studies of biogas production in a region need to be done carefully. The formulation waste power plant models with engine HCCI, is based on the reference model and reference experimental results of each part in the power plant waste that includes, production of biogas from landfill, biogas filter, generator power conversion HCCI. The production of biogas from landfills using multicomponent models, biogas filter using a filter system with a suspension of dolomite, and for the conversion of electricity using a generator HCCI referring to the results of experiments that has been conducted by Bedoya,2012. Waste power plant modeling result shows, if power output 3.725 .10-3 of capacity HCCI engine fuel consumption.